Modelling of plasma-wall interaction and impurity transport in fusion devices and prompt deposition of tungsten as application. (15th November 2017) - Kirschner, A; Tskhakaya, D; Brezinsek, S; Borodin, D; Romazanov, J; Ding, R; Eksaeva, A; Linsmeier, Ch
Abstract: Main processes of plasma-wall interaction and impurity transport in fusion devices and their impact on the availability of the devices are presented and modelling tools, in particular the three-dimensional Monte-Carlo code ERO, are introduced. The capability of ERO is demonstrated on the example of tungsten erosion and deposition modelling. The dependence of tungsten deposition on plasma temperature and density is studied by simulations with a simplified geometry assuming (almost) constant plasma parameters. The amount of deposition increases with increasing electron temperature and density. Up to 100% of eroded tungsten can be promptly deposited near to the location of erosion at very high densities (∼1 × 10 14 cm −3 expected e.g. in the divertor of ITER). The effect of the sheath characteristics on tungsten prompt deposition is investigated by using particle-in-cell (PIC) simulations to spatially resolve the plasma parameters inside the sheath. Applying PIC data instead of non-resolved sheath leads in general to smaller tungsten deposition, which is mainly due to a density and temperature decrease towards the surface within the sheath. Two-dimensional tungsten erosion/deposition simulations, assuming symmetry in toroidal direction but poloidally spatially varying plasma parameter profiles, have been carried out for the JET divertor. The simulations reveal, similar to experimental findings, that tungsten gross erosion is dominated in H-mode plasmas by the intra-ELM phases. However, due to deposition, the net tungsten erosion can be similar within intra- and inter-ELM phases if the inter-ELM electron temperature is high enough. Also, the simulated deposition fraction of about 84% in between ELMs is in line with spectroscopic observations from which a lower limit of 50% has been estimated.